STUDI PERKEMBANGAN PENELITIAN INDEKS KESEHATAN MANGROVE: STUDI PERKEMBANGAN PENELITIAN INDEKS KESEHATAN MANGROVE - Farid SM, Farid; Lihawa, Fitryane; Hasim; Wahyuni K. Baderan, Dewi ; Mahmud, Marike (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze the development trend of mangrove health index research in 2019-2024. The study of this research includes (1) the development of the number of international publications on the mangrove health index in the Science Direct database from 2019 to 2024; (2) the number of core journals in international publications on the mangrove health index; (3) the development of international publications on mangrove health index research based on subject / field; (4) the development map of international publications on mangrove health index research based on keywords (co-word). Data collection techniques by searching through science direct with the keyword Mangrove Health Index in the period 2019 to 2024 using the categories of article titles, abstracts, and keywords. Data analysis for the development trend of international publications in the field of mangrove health index was analyzed using VosViewer software. The results showed that research on mangrove health indexes developed rapidly between 2019 and 2024 indexed in Science Direct, the highest peak of publications was in 2023 with the number of publications reaching 500 publications (16.2%). The journal that publishes the highest mangrove health index is the Science of the Total Environment journal with 199 publications. Furthermore, based on VOSviewer analysis, the development of mangrove health index fields can be grouped into 7 main clusters.